UMP's data management system (E-Dash) emerged as winner in KPM innovation award (management category) 2014 - Noor Syahidah, Sabran (Penerbit UMP, 2014)
Universiti Malaysia Pahang (UMP) was recently announced winner of the Ministry of Education Innovation Award (AIKPM 2014) for the management category.